DAMPAK DISKRIMINASI PELAKSANAAN JADWAL PELAJARAN SEJARAH TERHADAP AKTIFITAS BELAJAR SISWA - Adela Siahaan (Universitas Riau Kepulauan, 2017)
AbstractThe research entitled the discrimination impact of history subject implementation toward students learning activity. This research used qualitative approach with case study method which did in SMA Negeri 14 Batam. Data collection techniques used observation and documentation of history learning; field notes, interviews with headmaster, vice-principal of curriculum, and students. Research results revealed that (1) discrimination that occurred in the implementation of history lesson because history subject just seen from the intellectual potential that is only the historical material. This causes history lesson is more often carried out during the daytime than science subject and the lessons which will be tested in national exam that dominated the schedule implementation in the morning (2) The implementation of schedule history in daytime causes students learning activity focused on listening and writing (3) The impact of discrimination implementation history schedule subject during daytime not just happen only for students but also the history teacher, that teacher are fatigue when teaching at daytime due to lack of history teacher at SMA negeri 14 Batam.Keywords : Discrimination, schedule, History Education, Activity. Abstrak Penelitian ini berjudul dampak diskriminasi dari penerapan subjek sejarah terhadap aktivitas belajar siswa. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus di SMA Negeri 14 Batam. Teknik pengumpulan data menggunakan observasi dan dokumentasi pembelajaran sejarah; Catatan lapangan, wawancara dengan kepala sekolah, wakil kepala sekolah, dan siswa. Hasil penelitian menunjukkan bahwa (1) diskriminasi yang terjadi dalam pelaksanaan pelajaran sejarah karena subjek sejarah hanya dilihat dari potensi intelektual yang hanya merupakan bahan sejarah. Hal ini menyebabkan pelajaran sejarah lebih sering dilakukan pada siang hari daripada pelajaran sains dan pelajaran yang akan diuji dalam ujian nasional yang mendominasi pelaksanaan jadwal di pagi hari (2) Penerapan riwayat jadwal di siang hari menyebabkan aktivitas belajar siswa terfokus pada pendengaran. Dan menulis (3) Dampak dari jadwal pelaksanaan riwayat pelaksanaan diskriminasi selama siang hari tidak hanya terjadi hanya untuk siswa tapi juga guru sejarah, bahwa guru kelelahan ketika mengajar di siang hari karena kurangnya guru sejarah di SMA negeri 14 Batam. Kata kunci: Diskriminasi, jadwal, Pendidikan Sejarah, Aktivitas.